Strategic Aspects of the European Experience as a Basis for Innovative Policy Forming in Ukraine (Economics and region, 2018)
The article is devoted to the problems of development of innovative policy of Ukraine taking into account European experience. The basic ways of perfection are considered after the indicated direction with the purpose of activation of innovative development of the state. Development of innovative potential of the European countries status is found out. The constituents of development of innovative policy of Ukraine are investigational. The theoretical and methodological going is systematized near development of innovative policy of Ukraine.
Keywords: public innovative policy; innovative activity; scientific and technical progress; national innovative system; programs of innovative development